Mortality as an indicator of quality of neurosurgical care in England: a retrospective cohort study. Issue 11 (4th November 2022) - Wahba, Adam J; Cromwell, David A; Hutchinson, Peter J; Mathew, Ryan K; Phillips, Nick
Abstract : Objectives: Postoperative mortality is a widely used quality indicator, but it may be unreliable when procedure numbers and/or mortality rates are low, due to insufficient statistical power. The objective was to investigate the statistical validity of postoperative 30-day mortality as a quality metric for neurosurgical practice across healthcare providers. Design: Retrospective cohort study. Setting: Hospital Episode Statistics data from all neurosurgical units in England. Participants: Patients who underwent neurosurgical procedures between April 2013 and March 2018. Procedures were grouped using the National Neurosurgical Audit Programme classification. Outcomes measured: National 30-day postoperative mortality rates were calculated for elective and non-elective neurosurgical procedural groups. The study estimated the proportion of neurosurgeons and NHS trusts in England that performed sufficient procedures in 3-year and 5-year periods to detect unusual performance (defined as double the national rate of mortality). The actual difference in mortality rates that could be reliably detected based on procedure volumes of neurosurgeons and units over a 5-year period was modelled. Results: The 30-day mortality rates for all elective and non-elective procedures were 0.4% and 6.1%, respectively. Only one neurosurgeon in England achieved the minimum sample size (n=2402) of elective cases in 5 years needed to detect if their mortality rate was double the national average. All neurosurgical units achieved the minimum sample sizes for both elective (n=2402) and non-elective (n=149) procedures. In several neurosurgical subspecialties, approximately 80% of units (or more) achieved the minimum sample sizes needed to detect if their mortality rate was double the national rate, including elective neuro-oncology (baseline mortality rate=2.3%), non-elective neuro-oncology (rate=5.7%), neurovascular (rate=6.7%) and trauma (rate=11%). Conclusion: Postoperative mortality lacks statistical power as a measure of individual neurosurgeon performance. Neurosurgical units in England performed sufficient procedure numbers overall and in several subspecialty areas to support the use of mortality as a quality indicator.